Properties of Electrospun Nanofibers of Multi-Block Copolymers of [Poly-ε-caprolactone-b-poly(tetrahydrofuran-co-ε-caprolactone)]m Synthesized by Janus Polymerization - Muhammad Ijaz Shah (Polymers, 2017)
Novel biodegradable multiblock copolymers of [PCL-b-P(THF-co-CL)]m with PCL fractions of 53.3 and 88.4 wt % were prepared by Janus polymerization of ε-caprolactone (CL) and tetrahydrofuran (THF). Their electrospun mats were obtained with optimized parameters containing bead-free nanofibers whose diameters were between 290 and 520 nm. The mechanical properties of the nanofiber scaffolds were measured showing the tensile strength and strain at break of 8–10 MPa and 123–161%, respectively. Annealing improved their mechanical properties and their tensile strength and strain at break of the samples increased to 10–13 MPa and 267–338%, respectively. Due to the porous structure and crystallization in nanoscale confinement, the mechanical properties of the nanofiber scaffolds appeared as plastics, rather than as the elastomers observed in bulk thermal-molded film.